Compensatory justice - Chapman, John W. (John William), 1923-2008 (Nomos ;, 1991)
"Began with presentations and commentaries at the meeting of The American Society for Political and Legal Philosophy held in conjunction with the annual meeting of the Association of American Law Schools in New Orleans, 5-8 January 1989"--Preface